Effect of naringerin on biochemical parameters in the streptozotocin-induced diabetic rats - Fernandes, Ana Angélica Henrique [UNESP]; Novelli, Ethel Lourenzi Barbosa [UNESP]; Fernandes Junior, Ary [UNESP]; Galhardi, Cristiano Machado [UNESP] (Brazilian Archives of Biology and Technology, 2009)
Dentre as numerosas terapias para minimizar as complicações diabéticas, os antioxidantes e flavonoides são testados na clínica médica. Foi analisado o efeito da naringerina sobre os parâmetros bioquímicos em ratos diabéticos induzidos por estreptozotocina (STZ - 60mg/kg, i.p.). Ratos machos foram divididos em 4 grupos: G1: controle não tratado; G2: ratos normais que receberam naringerina; G3: diabéticos não tratados; G4: ratos diabéticos que receberam naringerina. Naringerina (50mg/kg, i.p.), decresceu a hiperglicemia e a hiperlipidemia em ratos diabéticos. A concentração sérica de insulina em ratos tratados tendeu aumentar. A naringerina preveniu as alterações, provocadas pela estreptozotocina, na atividade hepática e cardíaca de ALT, AST e LDH, indicando o efeito protetor da naringerina sobre estes tecidos, contra toxicidade provocada pela STZ. O nível de glicogênio nos tecidos cardíaco e hepático elevou com a naringerina em ratos diabéticos. A naringerina melhorou o metabolismo da glicose e de lipídios e preveniu as complicações diabéticas.

Amongst the numerous co-adjuvant therapies which could influence the incidence and progression of diabetic complications, antioxidants and flavonoids are currently being tested in clinical trials. We investigated the effect of naringerin on biochemical parameters in streptozotocin-induced (STZ - 60 mg/kg, i.p.) diabetic rats. Male rats were divided into four groups: G1: untreated controls; G2: normal rats receiving naringerin; G3: untreated diabetics; G4: diabetics rats receiving naringerin. The naringerin (50mg/kg, i.p,) decreased the hyperglycaemia and hyperlipidaemia associated with STZ-diabetes. The concentrations of serum insulin in treated diabetic rats tended to be increased. Naringerin treatment prevents STZ-induced changes in the activities of ALT, AST and LDH in the liver and heart, indicating the protective effect of naringerin against the hepatic and cardiac toxicity caused by STZ. The glycogen level in cardiac and hepatic tissues elevated with naringerin in diabetic rats. The naringerin can improve the glucose and lipid metabolism and is beneficial in preventing diabetic complications.
Keywords: Naringerin; hypoglycaemic activity; streptozotocin; diabetes mellitus; aminotransferases; hepatic; cardiac tissues